Adaptive sliding mode control for deployment of electro-dynamic tether via limited tension and current. (December 2020) - Chen, Shumin; Li, Aijun; Wang, Changqing; Liu, Chenguang
Abstract: This paper studies the deployment control of the electrodynamic tether system by means of tether tension and electric current regulation. Design of the control strategy has been implemented based on the simplified dumbbell model. In order to improve the robustness of the control system to the possible external disturbances, an adaptive sliding mode control is proposed to deploy the tether to the local vertical with the consideration of input limitations, which are introduced by a pair of saturation functions to ensure that the tether tension is always non-negative and the current is within limits. In addition, the proposed adaptive law is intended to estimate the mass parameter of the model, which is with uncertainty caused by the difficulty in accurately determining the masses of the end-bodies. The stability characteristic of the system under the proposed hybrid controller is studied based on the Lyapunov theory. Numerical case studies in the different orbital inclinations are conducted to illustrate the effectiveness of the proposed control strategy. Moreover, the performance of the controller is presented in the presence of the initial perturbations, the external disturbances and the uncertainty of mass parameter of the system. Highlights: A hybrid deployment strategy for the electro-dynamic tether is investigated. The tether is deployed to the desired local vertical via limited tension and current regulation. The deployment controller has a strong ability of anti-disturbance. The unknown mass parameter of the system is well-estimated using the adaptive law.